Managerial Economics And Business Strategy - Baye Michael (Mcgraw Hill Book Company Bostan, 2006)
THE FUNDAMENTALS OF MANAGERIAL ECONOMICS AND MARKET FORCES DEMAND AND SUPPLY,THE NATURE OF INDUSTRY,ETC.
English
Keywords: Economics Managerial (B-13)